2019
DOI: 10.1016/j.envres.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of oil-spill cleanup participation following the Deepwater Horizon oil spill

Abstract: Background-On April 20, 2010, the Deepwater Horizon oil rig exploded, spilling over 4.9 million barrels of oil in the Gulf of Mexico over an 87-day period and developing into a long-term environmental disaster that affected people living in Gulf Coast states. Engagement of community members in recovery efforts is important for mitigating adverse effects of disasters and accelerating the rebuilding process for impacted communities; however, few studies have explored factors that determine participation in oil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Approximately 4.7% of residents in affected Gulf communities participated in the oil spill cleanup activities, and most were young men in excellent physical health [ 15 ]. These individuals residing in affected communities may have been easily mobilised and motivated to help their affected communities by participating in cleanup activities [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 4.7% of residents in affected Gulf communities participated in the oil spill cleanup activities, and most were young men in excellent physical health [ 15 ]. These individuals residing in affected communities may have been easily mobilised and motivated to help their affected communities by participating in cleanup activities [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing participation in disaster-related cleanup activities could also increase resilience and recovery of individuals and the surrounding community. 29 Although this cross-sectional study is limited in its ability to draw firm causal inferences, the findings from this paper raise the possibility that encouraging affected individuals to volunteer in times of need may mitigate the harmful effects of oil exposure. Further research, such as trials evaluating post-oil exposure cleanup participation as an intervention, is needed.…”
Section: Implications and Conclusionmentioning
confidence: 90%
“…A recent study examining determinants of participation in cleanup activities found positive associations of participation and proximity of affected areas. 29 Approximately 4.7% of residents in affected Gulf communities participated in the oil spill cleanup activities, and most were young men in excellent physical health. 29 These individuals residing in affected communities may have been easily mobilized and motivated to help their affected communities by participating in cleanup activities.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes to quality of life can be tracked by amount of green space created, reduction in fear or anxiety, or increase in aff ordable housing (Bacot and O'Dell 2006;Cappuyns 2016;Lange and McNeil 2004;Tonin 2014;Tuler et al 2007;Wedding and Crawford-Brown 2007). Cleanup volunteerism rates and related demographics of cleanup laborers could shed more light on how cleanups aff ect the workforce and labor practices (Sharpe et al 2019). Usage and user perceptions of postremediated sites could be collected to understand how cleanups may aff ect place-making (Heatherington et al 2019;Newman 2011).…”
Section: New Directions For Measuring Outcomesmentioning
confidence: 99%